The Role of Business Capital and Marketing Strategies in Supporting MSME Development in Sobontoro Village, Balen Subdistrict, Bojonegoro Regency - Moch. Ilham Abdul Aziz; Nanang Setiawan (Institut Agama Islam Al-Fatimah Bojonegoro, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in driving economic growth, yet their development often hinges on the effective use of business capital and marketing strategies. This study aims to explore the influence of business capital and marketing strategies on the growth of MSMEs. Using a qualitative descriptive method, the research focuses on three MSMEs in Sobontoro Village: a meatball and chicken noodle food stall, the Mliwis Putih Batik shop, and the MP Computer Berkah & Shaka Plastik shop. The findings reveal that sufficient business capital significantly impacts operational management and product competitiveness. Additionally, innovative marketing strategies, including social media and local promotions, effectively enhance product visibility and attract customers. Good capital management and appropriate marketing strategies are essential for achieving sustainable business growth and increasing market competitiveness. This study provides practical insights for MSME owners on the importance of optimizing capital management and adopting effective marketing strategies to advance their businesses. Furthermore, it contributes to the broader understanding of how MSMEs can enhance their resilience and competitiveness in local markets